Glutamate Deregulation in Ketamine-Induced Psychosis—A Potential Role of PSD95, NMDA Receptor and PMCA Interaction - Lisek, Malwina; Ferenc, Bozena; Studzian, Maciej; Pulaski, Lukasz; Guo, Feng; Zylinska, Ludmila; Boczek, Tomasz (Frontiers in Cellular Neuroscience, 2017)
Ketamine causes psychotic episodes and is often used as pharmacological model of psychotic-like behavior in animals. There is increasing evidence that molecular mechanism of its action is more complicated than just NMDA receptor antagonism and involves interaction with the components of calcium homeostatic machinery, in particular plasma membrane calcium pump (PMCA). Therefore, in this study we aimed to characterize brain region-specific effects of ketamine on PMCA activity, interaction with NMDA receptor through PSD95 scaffolding proteins and glutamate release from nerve endings. In our study, ketamine induced behavioral changes in healthy male rats consistent with psychotic effects. In the same animals, we were able to demonstrate significant inhibition of plasma membrane calcium ATPase (PMCA) activity in cerebellum, hippocampus and striatum. The expression level and isoform composition of PMCAs were also affected in some of these brain compartments, with possible compensatory effects of PMCA1 substituting for decreased expression of PMCA3. Expression of the PDZ domain-containing scaffold protein PSD95 was induced and its association with PMCA4 was higher in most brain compartments upon ketamine treatment. Moreover, increased PSD95/NMDA receptor direct interaction was also reported, strongly suggesting the formation of multiprotein complexes potentially mediating the effect of ketamine on calcium signaling. We further support this molecular mechanism by showing brain region-specific changes in PSD95/PMCA4 spatial colocalization. We also show that ketamine significantly increases synaptic glutamate release in cortex and striatum (without affecting total tissue glutamate content), inducing the expression of vesicular glutamate transporters and decreasing the expression of membrane glutamate reuptake pump EAAT2. Thus, ketamine-mediated PMCA inhibition, by decreasing total Ca2+ clearing potency, may locally raise cytosolic Ca2+ promoting excessive glutamate release. Regional alterations in glutamate secretion can be further driven by PSD95-mediated spatial recruitment of signaling complexes including glutamate receptors and calcium pumps, representing a novel mechanism of psychogenic action of ketamine.